The effect of the 4Ps marketing mix and e-WOM on Gen Z consumers' purchasing decisions: A case study at Chalissa Studio in Cianjur - Dhita Widya Ramadani; Yuli Novitasari; Riani Winarni (Priviet Social Sciences Journal, 2026)
This study aimed to evaluate how the 4Ps of the Marketing Mix and E-WOM influence Gen Z customers' purchasing behavior at Chalissa Studio. Using purposeful sampling, the quantitative method employed in this study involved administering a closed questionnaire to 100 participants. Instrument testing, classical assumption testing, multiple linear regression testing, hypothesis testing, and coefficient of determination testing (R2) were used to analyze the gathered data to ascertain the simultaneous and partial effects among variables. This research indicates that: (1) The product has a regression coefficient of 0.317 and a t-value of 12.672, both of which are positive and statistically significant; (2) Price has a substantial but unfavorable effect, as shown by the t-value of -13.079 and the regression coefficient of -0.810. (3) The location has a statistically significant and positive t-value of 2.080 and a regression coefficient of 0.044; (4) The regression coefficient for promotion is 0.272, and the t-value is 2.938, both of which are positive and statistically significant; (5) With a regression coefficient of 0.898 and a t-value of 16.974, which are both statistically significant and positive, E-WOM is said to be positive; (6) The 4P Marketing Mix and E-WOM with an F-value of 855.291; (7) The impact of the 4P Marketing Mix and E-WOM on purchase decisions is shown by the R Square value of 0.978, or 97.8%, with the other 2.2% being attributable to other factors not addressed in this research